Mediastinal Tuberculosis Lymphadenitis during Anti-TNF Therapy - Case Report - Bruno Cesar da Silva; Fabio Carneiro Vosqui Nascimento; Sonyara Rauedys Oliveira Lisboa; Eduardo Antonio Gonçalves Ramos; Valdiana Cristina Surlo; Tatiana Senna Galvão Nonato Alves; Genoile Oliveira Santana (Archives of Clinical Gastroenterology - Peertechz Publications, 2015)
Tuberculosis is described during the use of monoclonal antibodies against tumour necrosis factor (TNF) for Crohn's disease treatment. We report a case of a 44 year old man that developed fever, night sweats and weight loss during immunosuppressive and anti-TNF therapy for Crohn's disease. After extensive investigation we performed mediastinoscopy with biopsy of the paratracheal lymph node. A istopathological study revealed caseous necrosis. The patient improved after therapy against tuberculosis. During anti-TNF therapy, the diagnosis of tuberculosis may be mainly difficult when an atypical location is present. Clinical skills are important mainly in countries where tuberculosis is endemic.